Fabrication of Ibrutinib Nanosuspension by Quality by Design Approach: Intended for Enhanced Oral Bioavailability and Diminished Fast Fed Variability - Rangaraj, Nagarjun; Pailla, Sravanthi Reddy; Chowta, Paramesh; Sampathi, Sunitha (AAPS PharmSciTech, 2019)
Present study was aimed to increase the oral bioavailability and reduce the fast fed variability of Ibrutinib by developing nanosuspension by simple precipitation-ultrasonication method. A three factor, three level, box-behnken design was used for formulation optimization using pluronic F-127 as stabilizer. Size and polydispersity index of the developed formulations were in the range of 278.6 to 453.2 nm and 0.055 to 0.198, respectively. Field emission scanning electron microscope (FESEM) revealed discrete units of nanoparticles. Further, differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD) studies confirmed the transformation of crystal drug to amorphous. The amorphous nature was retained after 6-month storage at room temperature. Size reduction to nano range and polymorphic transformation (crystalline to amorphous) increased the solubility of nanosuspension (21.44-fold higher as compared to plain drug). In vivo studies of plain drug suspension displayed a significant pharmacokinetic variation between fasting and fed conditions. The formulation had shown increased C max (3.21- and 3.53-fold), AUC 0-t (5.21- and 5.83-fold) in fasting and fed states compared to that of values obtained for plain drug in fasting state ( C max 48.59 ± 3.30 ng/mL and AUC 0-t 137.20 ± 35.47 ng.h/mL). Significant difference was not observed in the pharmacokinetics of nanosuspension in fasting and fed states. The formulation had improved solubility in the intestinal pH, which might be the driving force behind the decreased precipitation and increased absorption at intestinal region. Optimistic results demonstrated nanosuspension as a promising approach for increasing the solubility, extent of absorption and diminishing the fast fed variability.